PERKEMBANGAN SOSIAL EKONOMI TRANSMIGRAN DI KAMPUNG TANJUNG GADANG KECAMATAN SUTERA KABUPATEN PESISIR SELATAN TAHUN 1994-2011 - Elvira, Wira; Ansofino, Ansofino; Kharles, Kharles (Pendidikan Sejarah, 2014)
Migrants is the person who first introduced the oil to the people in Tanjung Gadang Village. Nowadays the development of Tanjung Gadang Village including very rapidly, which today has grown palm plantations are very well known to the public and began in 1995. Therefore the problem is formulated as follows: Socio-Economic Development of Migrants in Tanjung Gadang Village Sutera District of Pesisir Selatan Region 1994-2011. This research includes the study of sosia economic history following research methods: (1) heuristic, (2) a source of criticism include internal and external criticism, (3) the interpretation of which is the activity, and (4) a the stage of writing a thesis result. The results showed: (1) transmigration in Tanjung Gadang Village was in 1994, there was 130 households from the island of Java. Throughout the years of 1998-2002 occurred a massive reduction in Tanjung Gadang Village, many migrants living in Tanjung Gadang Village palm planting. Then the rise in oil prices make the migrants of Tanjung Gadang Village grow palm. Another area that is cultivated by the community at the time was the farm, education of children today including migrants enough, the child of migrants had educated through college and graduated from high school in general. Migrants choose to utilize the facilities of health care at the health center at Surantih, even up to the hospital in Painan. Migrants in Tanjung Gadang Village marriage migrants generally do, but there is also the local community. Religious system, migrants are still affected by their habit in Java. Most of the migrants in Tanjung Gadang Village residents are members of the Java community, especially those in Tanjung Gadang Village is not interrupted with other migrants in Sumatera Barat. Exchange occurs in the form of subsistence, such as rice, side dishes and so on. Migrants are likely to need basic necessities such as rice because there is no rice in Tanjung Gadang Village complex migrants and the unavailability of other sources to meet the needs.